Science and meditation (2018)
This article shows the growing interest in the scientifically supported benefits of a powerful tool of mental, emotional and developmental training, known as meditation, and sometimes as Mindfulness. To talk about these benefits it is found a brief explanation of the history of meditation in the West and the history of research on this subject which shows the huge explosion of research that is generated when it begins to unveil its potential to improve the physical, mental, emotional, cognitiveand social health of the individuals who use it.